Analisis Efektivitas Penggunaan Quiziz Menggunakan Technology Acceptance Model Pada SMP XXX Penajam - Shabraniti, Zulmajedi Ihza Mahendra; Utamajaya, Joy Nashar (LPPM UNIKA Santo Thomas Medan, 2024)
This study aims to analyze the effectiveness of using Quizizz in learning at SMP XXXX Penajam by employing the Technology Acceptance Model (TAM). The model eval_uates factors such as perceived ease of use (PEOU) and perceived usefulness (PU) to understand students’ attitudes toward using Quizizz. Data were collected through surveys of 80 students and analyzed using Structural Equation Modeling (SEM). The results reveal that PEOU significantly influences PU, which subsequently affects students’ intentions to use Quizizz. Quizizz has been proven to enhance students' motivation and understanding of the lesson material. This study provides insights into the importance of educational technology in creating more interactive and effective learning experiences.